Pathogenesis and Novel Treatment from the Mouse Model of Type 2 Diabetic Nephropathy. (24th April 2013) - Furukawa, Masako; Gohda, Tomohito; Tanimoto, Mitsuo; Tomino, Yasuhiko
Abstract : Diabetic nephropathy (DN) is the leading cause of end-stage kidney disease worldwide. However, current treatments remain suboptimal. Many factors, such as genetic and nongenetic promoters, hypertension, hyperglycemia, the accumulation of advanced glycation end products (AGEs), dyslipidemia, and albuminuria/proteinuria itself, influence the progression of this disease. It is important to determine the molecular mechanisms and treatment of this disease. The development of diabetes results in the formation of AGEs, oxidative stress, and the activation of the renin-angiotensin-aldosterone system (RAAS) within the kidney, which promotes progressive inflammation and fibrosis, leading to DN and declining renal function. A number of novel therapies have also been tested in the experimental diabetic model, including exercise, inhibitors of the RAAS (angiotensin type 1 receptor blockers (ARB), angiotensin-converting enzyme (ACE) inhibitors), inhibitors of AGE (pyridoxamine), peroxisome proliferator-activated receptor (PPAR) γ agonists (pioglitazone), inhibitors of lipid accumulation (statins and eicosapentaenoic acid (EPA)), and the vitamin D analogues. This review summarizes the advances in knowledge gained from our studies and therapeutic interventions that may prevent this disease.